2016
DOI: 10.1177/1479164116651389
|View full text |Cite
|
Sign up to set email alerts
|

Negative association of diabetes with rupture of abdominal aortic aneurysm

Abstract: Purpose: To summarize the association of diabetes with abdominal aortic aneurysm rupture, we reviewed currently available studies with a systematic literature search and meta-analytic evaluation. Methods: To identify all studies reporting the association of diabetes with abdominal aortic aneurysm rupture, MEDLINE and EMBASE were searched through July 2015. For each study, data regarding diabetes prevalence in both the ruptured and non-ruptured groups were used to generate an unadjusted odds ratio for abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 30 publications
3
33
1
Order By: Relevance
“…As large aortic diameter and high growth rate represent major risk factors of rupture, 7 it is not surprising that a negative association between DM and aneurysm rupture was identified. 20 …”
Section: Diabetes and The Epidemiology Of Aortic Aneurysmmentioning
confidence: 99%
“…As large aortic diameter and high growth rate represent major risk factors of rupture, 7 it is not surprising that a negative association between DM and aneurysm rupture was identified. 20 …”
Section: Diabetes and The Epidemiology Of Aortic Aneurysmmentioning
confidence: 99%
“…In addition, several reports have shown that diabetic patients develop smaller aneurysm and have lower growth rates of AAA ( 6 , 8 , 13 - 17 ). At last, a negative association was found between diabetes and AAA rupture ( 18 ). These results suggest a protective effect of diabetes on AAA formation and the understanding of the mechanisms involved could bring innovative therapeutic strategies for the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in a variety of populations have reported a strong negative association between diabetes and AAA prevalence, growth and rupture. The cause of this negative association is unknown, but one suggested reason is that medications prescribed to patients to control hyperglycaemia may have pleiotropic effects that could influence AAA growth.…”
Section: Introductionmentioning
confidence: 99%